PENGHAYATAN PASUTRI KATOLIK TENTANG SIFAT PERKAWINAN KATOLIK YANG MONOGAM DAN TAK TERCERAIKAN - Yupita, Yuta; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2020)
This study aims to describe the Catholic spouses’ views on the unity and indissolubility of Christian marriage and how they live out these essential properties in their marital life. The research was conducted using a qualitative approach with purposive sampling to select informants, consisting of Catholic couples who have been married for more than 20 years. Data were collected through in-depth interviews. The study took place in a Catholic parish community in Indonesia. The findings revealed two main conclusions. First, the Catholic spouses understand the unity and indissolubility of marriage as a sacred covenant grounded in their faith and commitment before God. Second, they strive to live out these values consistently in daily life, demonstrating fidelity, mutual support, and perseverance despite life’s challenges.